Association between perceived neighborhood environment and health of middle-aged women living in rapidly changing urban Mongolia - Tserendulam Shagdarsuren; Keiko Nakamura; Layla McCay (Komiyama Printing Co. Ltd, 2017)
Abstract Background This study was conducted in rapidly urbanizing Ulaanbaatar, Mongolia, to examine patterns of perceived neighborhood quality by residents and the associations between these patterns and self-reported general and mental health in middle-aged women. Methods A questionnaire survey was administered to 960 women aged 40-60 years. Demographic and socio-economic characteristics, subjects' perception of their neighborhood environment, general health status, and mental health as measured using a 12-item General Health Questionnaire (GHQ12) were reported. Results A total of 830 women completed the questionnaire. Subjects reporting their general health as very good or good accounted for 80.3% and those with a GHQ12 ≥16, which reflects psychological distress or severe distress, accounted for 16.1%. A principal component analysis of the perceptions of neighborhood environment by the residents identified six qualities: physical environment, designed environment, neighborhood community, public safety, natural environment, and citizen services. The perception of better-quality citizen services in the neighborhood was associated with better self-reported general health (odds ratio [OR] = 1.330, 95% confidence interval [CI] 1.093-1.618), and the perception of better-quality public safety was associated with less psychological distress (OR = 0.718, 95% CI 0.589-0.876); these associations were independent of education, income, occupation, type of residential area, and number of years living in the current khoroo. Conclusions The perception of the quality of a neighborhood environment can affect the self-reported general and mental health of residents, even after accounting for the type of residential area and individual socio-economic status. Developing high-quality neighborhoods is an essential component of good planning to promote population health in urban environments.